2010
DOI: 10.1073/pnas.0914795107
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species–independent activation of the IL-1β inflammasome in cells from patients with chronic granulomatous disease

Abstract: Humans with chronic granulomatous diseases (CGDs) due to mutations in p47-phox have defective NADPH activity and thus cannot generate NADPH-dependent reactive oxygen species (ROS). The role of ROS in inflammation is controversial; some in vitro studies suggest that ROS are crucial for secretion of IL-1β via inflammasome activation, whereas mice defective for ROS and patients with CGD have a proinflammatory phenotype. In this study, we evaluated activation of the IL-1β inflammasome in cells from CGD patients. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
169
3
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(186 citation statements)
references
References 35 publications
10
169
3
4
Order By: Relevance
“…31 More recently, it was shown in patients that Phox deficiency caused increased caspase-1 activity and IL-1b generation. 32,33 However, this issue remains a matter of debate, because several groups showed that ROS had either no effect or an accelerating effect on inflammasome-mediated IL-1b. [34][35][36] Furthermore, the ROS source and the specific ROS molecule that controls inflammasome activity are not yet characterized.…”
Section: Discussionmentioning
confidence: 99%
“…31 More recently, it was shown in patients that Phox deficiency caused increased caspase-1 activity and IL-1b generation. 32,33 However, this issue remains a matter of debate, because several groups showed that ROS had either no effect or an accelerating effect on inflammasome-mediated IL-1b. [34][35][36] Furthermore, the ROS source and the specific ROS molecule that controls inflammasome activity are not yet characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in monocytes and macrophages established that caspase-1 activity is negatively regulated by cysteine oxidation [12,28]. As pro-IL-1β processing takes place before mature IL-1β is released from cells by the ROS-dependent mechanism described above, we reasoned that if neutrophil caspase-1 is also regulated by oxidation, the addition of superoxide before neutrophil stimulation should inhibit pro-IL-1β processing and consequently IL-1β secretion.…”
Section: Ros Also Negatively Regulate Neutrophil Pro-il-1β Processingmentioning
confidence: 99%
“…*P , .05, **P , .01, ****P , .0001. IL-1b when stimulated in vitro with particulate and soluble activators of caspase-1 and NLRP3 inflammasome, 44,47,48 and 1 study reported increased IL-1a release by LPS-stimulated human CGD monocytes. 47 Here, we showed that NADPH oxidase deficiency augmented IL-1a and IL-1b release from murine resident macrophages, BMDMs, and BMDCs challenged with classic DAMPs that activate the NLRP3 inflammasome.…”
Section: Org Frommentioning
confidence: 99%